2021
DOI: 10.1093/brain/awab122
|View full text |Cite
|
Sign up to set email alerts
|

Reactive microglia enhance the transmission of exosomal α-synuclein via toll-like receptor 2

Abstract: Increasing evidence suggests that microglial activation is strongly linked to the initiation and progression of Parkinson’s disease (PD). Cell-to-cell propagation of α-synuclein (α-syn) pathology is a highlighted feature of PD, and the focus of such research has been primarily on neurons. However, recent studies as well as the data contained herein suggest that microglia, the primary phagocytes in the brain, play a direct role in the spread of α-syn pathology. Recent data revealed that plasma exosomes derived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
58
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(60 citation statements)
references
References 56 publications
1
58
1
Order By: Relevance
“…In addition, the clinical presentation was in contrast to our critically ill patient with poor neurological status; the latter is the emerging phenotype of COVID-19 leukoencephalopathy (Novi et al 2020 ). Of note, reports in the COVID-19 pandemic of other parainfectious immune-mediated neurological conditions such as cytotoxic lesions of the corpus callosum and Guillain-Barré syndrome remain relatively sparse considering the worldwide prevalence (Xiong et al 2021 ). However, that does not discount ADEM as a possibility in our case where a clinical response was seen following immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the clinical presentation was in contrast to our critically ill patient with poor neurological status; the latter is the emerging phenotype of COVID-19 leukoencephalopathy (Novi et al 2020 ). Of note, reports in the COVID-19 pandemic of other parainfectious immune-mediated neurological conditions such as cytotoxic lesions of the corpus callosum and Guillain-Barré syndrome remain relatively sparse considering the worldwide prevalence (Xiong et al 2021 ). However, that does not discount ADEM as a possibility in our case where a clinical response was seen following immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…A wide spectrum of neurological disease is recognized in COVID-19 from mild to severe presentations (Mao et al 2020 ; Xiong et al 2021 ). We report two patients with severe respiratory failure and poor neurological status with novel subacute radiological findings that yield insight into the pathogenesis of COVID-19 leukoencephalopathy.…”
Section: Introductionmentioning
confidence: 99%
“…TLR2. 94 Recently, Izco et al 95 investigated the temporal relationship between αSyn and inflammation in a mouse model of PD. They found that the peak expression of Iba1-positive microglia, GFAP-positive astrocytes, and IL-1β occurred before αSyn accumulation.…”
Section: Jmdmentioning
confidence: 99%
“…Furthermore, several researchers have been able to block or suppress microglial activation using pharmacological drugs and thereby have identified decreases in αSyn pathology in a mouse model. 17,94 There is also evidence that astrocytes actively transfer aggregated αSyn to healthy astrocytes through direct contact or tunneling nanotubes. 41,96 Ngolab et al 97 demonstrated that DLB brainderived exosomes trigger αSyn accumulation in astrocytes in the mouse brain, suggesting the participation of astrocytes in αSyn transmission.…”
Section: Jmdmentioning
confidence: 99%
“…During neuronal transmission of α-synuclein, microglia senses, engulfs and clears the extracellular α-synuclein to maintain the homeostasis in the brain (30,31). Several microglial receptors such as TLR2, TLR4, CD11b, FcγRIIB have been reported to interact with αsynuclein and its strains further induce pro-inflammatory microglia response [32,33,34,35].…”
Section: Introductionmentioning
confidence: 99%